Shape Memory Alloys Processing, Characterization and Applications - Manuel Braz Fernandes, Francisco (IntechOpen, 2013)
Shape memory alloys have become in the past decades a well established research subject. However, the complex relations between properties and structure have created a continuously growing interest for a deeper insight all this time. The complexity of relationships between structure and properties is mostly related to the fact that strong ?multidimensional? interactions are taking place: from the early studies focusing on the thermal and/or mechanical induced phase transformations to the more recent findings on the magnetically induced structural changes. On the other hand, these singular behavioral characteristics have driven a great industrial interest due to the innovative aspects that the applications of shape memory alloys may provide. This makes this subject a highly attractive source of continuous studies, ranging from basics crystallography and thermodynamics to mechanical analysis and electrical and magnetic properties characterization. In this book, a group of recent studies is compiled focusing on a wide range of topics from processing to the relationship between the structure and properties, as well as new applications.